Parking lot management system - Nor Syafiqah, Mat Yusoff (2019)
Nowadays, parking at shopping malls is one of the problems faced by the public. Most cars that want to park within the shopping complex need the drivers to take parking ticket on the machine provided at the entrance gate in shopping complex. This causes congestion at the entrance gate of shopping complexes especially at peak times such as weekends and public holidays as many people come to the centre of the shopping complex. Therefore, the objective of implementing the new system is to improve the existing system with the drivers need to scan the provided smart card and facilitate the driver to locate the parking space using the Radio Frequency Identification (RFID). The system also involves Arduino Mega and a parking sensor that will detect the parking if it has vacant space or not. Arduino will interact with Bluetooth module to make it easier for users to use the system which is easily for them to locate the parking by using their smart phones. The administrator also can manage registered user information in the parking lot.